Enhanced tenogenic potential of tendon-derived mesenchymal stem cells: transcriptomic profiling and in vivo validation - Khaled, Hadeer; Zayed, Mohammed; Kim, Bumseok; Jeong, Byung-Hoon; Oh, Sang-Ik (Frontiers in Cell and Developmental Biology, 2025)
Tendon injuries represent a significant clinical challenge in the treatment of musculoskeletal disorders due to their restricted intrinsic regenerative capacity and propensity for scar tissue formation. Tendon-derived mesenchymal stem cells (TD-MSCs) are considered a promising therapeutic approach because of their ability to differentiate into tenocytes, modulate inflammation, and secrete trophic factors that facilitate tendon regeneration. However, the molecular mechanisms underlying their effects and therapeutic advantages over other MSC sources remain unclear. This study aimed to elucidate the molecular basis of the therapeutic potential of TD-MSCs through a comprehensive transcriptomic comparison with bone marrow-derived MSCs (BM-MSCs) and evaluate their tenogenic differentiation capacity and regenerative efficacy. We isolated and characterized TD-MSCs and BM-MSCs using flow cytometry, tri-lineage differentiation assays, and proliferation assays (CCK-8) and examined their transcriptomic profiles via RNA sequencing. Subsequently, the tenogenic differentiation potential of TD-MSCs was evaluated in vitro by analyzing the expression of key markers (SCX, COL1, COL3, TN-C, TNMD, DCN, THBS-4, and SOX9) using quantitative reverse transcription-polymerase chain reaction, along with protein levels of SCX, COL1, and COL3 via immunofluorescence. The therapeutic efficacy of TD-MSC treatment was further tested in vivo using a rat model of Achilles tendon injury, with histological and immunohistochemical analyses performed for 6 weeks post-injection. The results showed that TD-MSCs exhibited superior proliferation and a distinct transcriptomic profile, with significantly elevated expression levels of tenogenic genes (COL1 and TN-C) compared to those observed in BM-MSCs. Following tenogenic induction, TD-MSCs showed enhanced differentiation capacity, with increased expression of tenogenic markers and downregulation of chondrogenic markers. In vivo treatment with TD-MSCs improved collagen fiber organization, enhanced structural integrity, and resulted in superior healing outcomes compared to untreated controls. These findings suggest that TD-MSCs possess intrinsic molecular advantages for tendon repair, characterized by enhanced tenogenic gene expression profiles relative to BM-MSCs and superior reparative potential both in vitro and in vivo. This study highlights the therapeutic potential of TD-MSCs for tendon regeneration and provides scientific evidence supporting tissue-specific MSC selection strategies for application in regenerative medicine.